2013
DOI: 10.2739/kurumemedj.ms63003
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Acute Pancreatitis Following Endoscopic Biopsy of the Ampulla of Vater

Abstract: Ampullary tumors are diagnosed by endoscopic biopsy of the ampulla of Vater. We encountered a rare case of acute pancreatitis following endoscopic biopsy of the ampulla. A 53-year-old man referred to our hospital for detailed examination of a suspected tumor of the ampulla of Vater. We conducted endoscopic biopsy from the ampulla. He developed severe abdominal pain four hours after the procedure. The serum amylase and serum lipase were elevated and abdominal computed tomography (CT) revealed pancreatic enlarge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
3
9
0
Order By: Relevance
“…The edema may have led to increased pancreatic duct pressure. This same mechanism is also proposed by Ishida et al [5] and Morales and Hixson [3], who reported cases of acute pancreatitis following endoscopic biopsy of the ampulla. Ishida et al [5] additionally mentioned that the rise in the pancreatic duct pressure must have been low and of short duration, as no dilation of the pancreatic duct was observed.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The edema may have led to increased pancreatic duct pressure. This same mechanism is also proposed by Ishida et al [5] and Morales and Hixson [3], who reported cases of acute pancreatitis following endoscopic biopsy of the ampulla. Ishida et al [5] additionally mentioned that the rise in the pancreatic duct pressure must have been low and of short duration, as no dilation of the pancreatic duct was observed.…”
Section: Discussionsupporting
confidence: 73%
“…The third was also a case of severe pancreatitis with formation of a large pancreatic walled-off necrosis that was managed with ultrasonography-guided drainage [5]. …”
Section: Discussionmentioning
confidence: 99%
“…The complication rate in both groups was consistent with the established complication rate with ERCP [ 6 , 7 , 13–15 ]. Another uncontrolled, smaller study [ 4 ], as well as case reports [ 9–11 ] on ampullary biopsy complications after ERCP, was in keeping with these findings. Our data agreed with the largest uncontrolled series reporting no complications with ampullary biopsies in a retrospective review of 62 patients undergoing ERCP for pancreatobiliary cancer or IgG-4 sclerosing cholangitis; however, post-procedure follow-up was not evaluated in that study [ 9 ].…”
Section: Discussionsupporting
confidence: 68%
“…Another uncontrolled, smaller study [ 4 ], as well as case reports [ 9–11 ] on ampullary biopsy complications after ERCP, was in keeping with these findings. Our data agreed with the largest uncontrolled series reporting no complications with ampullary biopsies in a retrospective review of 62 patients undergoing ERCP for pancreatobiliary cancer or IgG-4 sclerosing cholangitis; however, post-procedure follow-up was not evaluated in that study [ 9 ]. No study has evaluated ampullary biopsy during ERCP as an independent risk factor in the context of post-ERCP complications.…”
Section: Discussionsupporting
confidence: 68%
“…Only two previous cases of pancreatitis following ampullary biopsy exist in the literature; in only one did the patient develop pancreatic necrosis. 4,5 In previous cases, the proposed pathophysiological basis for the development of pancreatitis after biopsy was pressure on the pancreas due to intramural or submucosal oedema/haematoma following the biopsy although this was not confirmed on imaging. This is also the likely mechanism in our case.…”
Section: Discussionmentioning
confidence: 99%